Odpiranje javnih podatkov v podporo odločanju v slovenskem kmetijstvu - Kerstein, Maša (Časopis za kritiko znanosti, 2021)
The article is focused on the (non) use of data in public debate and decision-making processes, using the (common) agricultural policy in Slovenia as an example. Studies conducted within the scope of the Research Data Alliance show that descriptions of data sources and structures for the discovery, access, interoperability and re-use of data play an important role from a technical aspect, as well as in terms of content. The actual demand for data is also an important factor to consider. Studying public administrative data in the field of agriculture in Slovenia reveals a limited "supply" in terms of documentation, inclusion in catalogues, and equipping data to ensure connectivity and access solutions. At the same time, it appears that changes in "demand" at the EU level such as the strengthening of societal policy objectives, the increased flexibility of measures, and the justification of decisions with "facts", could be leveraged to strengthen the use of data in decision-making processes.
Keywords: administracija; FAIR; kmetijstvo; metapodatki; odprti podatki; računalniška semantika; semantika; Skupna kmetijska politika